Immune checkpoint inhibitor-associated diabetic ketoacidosis and insulin-dependent diabetes: a case report - Yungee Jung; Anthony Lau; Joseph Bednarczyk (Journal of Medical Case Reports)
Abstract Background Immunotherapy, including the use of immune checkpoint inhibitors such as nivolumab, is increasingly common in cancer treatment and can lead to various immune-related adverse effects, including rare cases of diabetic ketoacidosis. This case report highlights an unique instance of nivolumab-induced diabetic ketoacidosis in a patient without prior history of diabetes, emphasizing the importance of careful monitoring even in those without traditional risk factors. Case presentation We report a case of a 70-year-old Caucasian male with metastatic esophageal adenocarcinoma who developed diabetic ketoacidosis 3 weeks after stopping nivolumab therapy. The patient had no previous history of diabetes, nor had he used sodium–glucose transport protein 2 inhibitors or corticosteroids. Diagnostic tests confirmed diabetic ketoacidosis, and while he was initially treated following the institutional protocol, he continued to require insulin therapy indefinitely. Conclusions This case report underscores the risk of diabetic ketoacidosis linked to nivolumab, even in patients without predisposing factors, emphasizing the need for increased vigilance among both oncologists and physicians. It highlights the importance of monitoring for new-onset diabetes and diabetic ketoacidosis, whether immunotherapy is active or discontinued, and ensuring comprehensive care including hospitalization, insulin management, and diabetes education if diabetic ketoacidosis is diagnosed.